Design of a Visual Communication System for Animated Characters in Virtual Reality Using Sobel Edge Detection and Motion Capture - Zhengyu Yang (Journal of Applied Science and Engineering, 2025)
This study designs an animated character visual communication system appropriate for a virtual reality environment in order to address the issue of poor motion continuity of animated characters caused by inadequate edge data detection in the current visual communication system. Through three main design processes-target optimization, graphic image restructuring, and refinement-the system enhances the impact of graphic image processing in visual communication design by integrating image processing, visual image processing, and text processing technologies. The system uses the Hilditch algorithm for edge refining and the Sobel edge detection operator to increase the accuracy of edge data recognition. Comparing simulation testing reveals that the design system produces more realistic and coherent animated character motion than the current method. In addition to offering a fresh approach and point of reference for visual communication technology in animated character design, the system enables the precise recognition and continuous motion simulation of graphic representations in virtual reality.